Functions, accumulation, and biosynthesis of important secondary metabolites in the fig tree (Ficus carica) - Wang, Yawen; Liu, Ximeng; Chen, Siyu; Wang, Qingjie; Jin, Biao; Wang, Li (Frontiers in Plant Science, 2024)
Ficus carica is an economically important horticultural plant. Due to its abundant secondary metabolites, F. carica has gained interest for its applications in medicine and as a nutritional supplement. Both external and internal factors affect the accumulation of secondary metabolites in F. carica. The assembly of the F. carica genome has facilitated functional analysis of key genes and transcription factors associated with the biosynthesis of secondary metabolites, particularly anthocyanin.In this review, we summarize the various types and functions of secondary metabolites, with a particular focus on flavonoids, coumarins, and terpenes. We also explore the factors influencing their biosynthesis and accumulation, including varieties, tissue, environmental factors (e.g., light), stresses (e.g., high temperature, low temperature, drought, nutrient deficiencies, salinity), hormonal treatments, and developmental factors. Furthermore, we discuss the involvement of structural genes and transcription factors in the biosynthesis of secondary metabolites, specifically anthocyanin and furanocoumarins, knowledge of which will promote the breeding and genetic engineering of novel F. carica varieties.